Design, Synthesis, and Acetylcholinesterase Inhibition Assay of Novel 9-(1-(Substituted-benzyl)piperidin-4-yl)-2-chloro-9H-purin-6-amine Derivatives - Dongwei Kang; Yu'ning Song; Peng Zhan; Qingzhu Zhang; Xinyong Liu (Journal of Chemistry)
A new series of 9-(1-(substituted-benzyl)piperidin-4-yl)-2-chloro-9H-purin-6-amine derivatives were designed, synthesized, and characterized on the basis of 1H-NMR, 13C-NMR, and mass spectra. The newly synthesized compounds were evaluated for the inhibition activity against acetylcholinesterase (AChE). Biological results revealed that four compounds among them showed moderate activities against AChE with inhibitory percentage more than 10% at 100 μM. Further pharmacology investigation towards other pathological routes in AD is currently underway.